2021
DOI: 10.1071/an20171
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Australian sheep parasite control practices: a national online survey

Abstract: Context The third Australian national survey on control practices for internal and external parasites of sheep, following similar surveys in 2003 and 2011. Aims To document current parasite control practices and attitudes, measure change and to provide a benchmark against which to assess future practices and attitudes. Methods An online survey emailed to 6460 sheep producers, with a paper version supplied on request. A follow up short survey was conducted to assess non-response bias. Analysis by region and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…This issue is particularly significant for dicyclanil given its dominance in the flystrike chemical control market. 3 While the likely impact of the in vitro imidacloprid resistance observed in the present study on protection periods for flystrike products is unknown, a comparison of our data with those of Sales et al 5 indicates that the protection period for dicyclanil would likely be significantly reduced for the Walgett strain. Given the current reliance of the sheep industry on insecticidal control of flystrike, there is clearly a need to manage the use of insecticides such that the rate at which resistance develops to the currently-available chemicals is minimized.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…This issue is particularly significant for dicyclanil given its dominance in the flystrike chemical control market. 3 While the likely impact of the in vitro imidacloprid resistance observed in the present study on protection periods for flystrike products is unknown, a comparison of our data with those of Sales et al 5 indicates that the protection period for dicyclanil would likely be significantly reduced for the Walgett strain. Given the current reliance of the sheep industry on insecticidal control of flystrike, there is clearly a need to manage the use of insecticides such that the rate at which resistance develops to the currently-available chemicals is minimized.…”
Section: Discussionmentioning
confidence: 46%
“…in highlighting the emerging issue of resistance to the currently‐used insecticides in the sheep blowfly. This issue is particularly significant for dicyclanil given its dominance in the flystrike chemical control market 3 . While the likely impact of the in vitro imidacloprid resistance observed in the present study on protection periods for flystrike products is unknown, a comparison of our data with those of Sales et al 5 .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Sales et al 41 conducted an in vivo sheep trial with a highly dicyclanil‐resistant strain and found that flystrike protection periods for dicyclanil‐ and cyromazine‐based products were significantly reduced compared to product label guidelines (for example, label protection period of 18–24 weeks reduced to <11 weeks for dicyclanil). This evidence for resistance impacting on the period of protection of dicyclanil‐based products is particularly significant for the sheep industry given the dominant position of this chemical in the sheep flystrike control market: Colvin et al 42 reported that 40% of producers used this chemical, while Sales 39 found that of those producers who had used chemical recently, 56% had used dicyclanil. Cyromazine, which was also shown to have reduced protection periods when used against a resistant strain by Sales et al, 41 was the second most‐commonly used product according to both Colvin et al 42 at 24% and Sales 39 at 15%.…”
Section: Chemical Resistance: Current Statusmentioning
confidence: 99%
“…A recent review of current flystrike control practices in the Australian sheep industry found the most commonly used chemical was dicyclanil (40% of producers) followed by cyromazine (24%), ivermectin (12%) and spinosad (12%), indicating a high industry reliance on two structurally related compounds, dicyclanil and cyromazine. 6 However, recent studies have indicated that resistance to these two compounds is emerging in field blowfly populations. Cyromazine was used widely in the sheep industry for over 30 years before Levot 7 reported that larvae recovered from a property in southern NSW showed resistance to this compound, and to dicyclanil to a lesser extent, in in vitro assays.…”
Section: Insecticidesmentioning
confidence: 99%